Paciente con Hemorragia Digestiva Alta por Varices Esofágicas - Iglesias Falconi, Estefani Gabriela (2018)
High digestive hemorrhage due to esophageal varices is the product of increased portal vein pressure or portal hypertension. Hemorrhage due to rupture of esophageal varices is a serious and frequent complication in patients with liver cirrhosis. This has become a health problem because between 40-50% of patients suffering from liver cirrhosis have esophageal varices at the time are diagnosed. The objective of this work is to apply the nursing care process to a patient with upper gastrointestinal bleeding due to esophageal varices at the Luis Vernaza Hospital in the city of Guayaquil in order to identify the needs that are interfered with and establish care plans for improvement of the health conditions of the individual, respecting the dignity and the unity of the patient. The nursing care process was used as it is a scientific methodology which helped us to systematize interventions and personalize care for patients diagnosed with upper gastrointestinal bleeding due to esophageal varices, thus improving hemodynamics, quality of care, and time contributing to its recovery. In the elaboration of the nursing care process through the use of NANDA nurses, NIC NOC, it allowed us to provide holistic and humanized care, and communicate in a common language among the nurses to be able to act effectively in the specific care of the patient, since it serves us in our professional life as a Bachelor of nursing.